SLANG KALANGAN REMAJA PECINTA KOREA DALAM KOMUNITAS BTS FANBASE INDONESIA DI JEJARING SOSIAL TWITTER - Evi Cahyati; Fitri Amalia; Agus Milu Susetyo (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
Slang is informal, non-standard or unofficial language, which is seasonal, which is used for the internal needs of a particular social group with the intention of not being understood by people who are not members of that group. The aim of this research is to describe the form of slang among Korean-loving teenagers on the Twitter social network. This research uses language research methods, namely qualitative. This research data is in the form of speech in the BTS Fanbase Indonesia community which is classified according to the problem formulation created, namely regarding the form of slang language variations. The source of data obtained from this research comes from the stories of teenagers who love Korea in the BTS Fanbase Indonesia community on the Twitter social network. The data collection technique in this research is documentation in the form of listening techniques and note-taking techniques. The data collection instrument that researchers will use in this research is the researcher himself. In this research, the intralingual equivalent method is used, namely a method that refers to the meaning of elements in the language. In this case, data analysis is presented by describing the forms of slang variations used in the speech of Korean-loving teenagers on the Twitter social network